Local government engagement with climate change adaptation in Uganda - Esbern Friis-Hansen; Charles Aben; John James Okiror; Bernard Bashaasha; Godfrey Suubi (Danish Institute for International Studies (DIIS), 2015)
[Aims and Methodology of the CCRI Research Program] This DIIS Report will present selected findings from the results of the CCRI's research in Uganda. Climate Change and Rural Institutions (CCRI) is a joint collaborative research project (2012-2015) between the Danish Institute for International Studies (DIIS) and the Department of Agribusiness and Natural Resource Economics at Makerere University (Uganda), the IWRM Centre at the University of Zambia (Zambia), the Centre for Climate Change Studies at the Hué University of Agriculture and Forestry (Vietnam) and Forest Action (Nepal) with support from the Danish International Development Agency (DANIDA). The CCRI Uganda research team consists of three senior researchers, a PhD student and four research assistants. Qualitative interview results from key stakeholders and oral presentations during the CCRI district inception workshops and a joint CCRI/NAADS regional climate change adaptation workshop were recorded, transcribed and analysed using Nvivo software. The overall objective of the CCRI research program is to improve adaptation to climate change in rural areas through the development of policies to stimulate innovation among meso-level institutional actors. The research addresses the knowledge gap that currently exists regarding the role of district-level institutions in providing an enabling environment for climate change adaptation by rural citizens. These meso-level (district) institutions play a key role at the interface between national policies and individual/community-level adaptation efforts. The research program therefore explores (i) the nature and extent of their involvement and interactions in climate change adaptation, and (ii) the factors and processes that stimulate, constrain or block innovation in relation to climate change adaptation. The CCRI research program uses a qualitative fieldwork methodology that analyses case studies within their past and present political, economic and environmental contexts at the national and district levels. The foci of the case studies have been governance and institutions, including the historical development of national policies related to different aspects of decentralisation and the role of meso-level institutions, and their impact on the organisational cultures, cooperation and room for manoeuvre within these organisations. [...]
Keywords: 300